Idiopathic granulomatous hypophysitis: A report of an uncommon disorder - Shubhangi Vinayak Agale; Rachana Binayke; Geeta Kumari; Grace F D'Costa (Wolters Kluwer Medknow Publications, 2018)
Hypophysitis of the pituitary gland is a rare inflammatory disorder and broadly classified as primary and secondary hypophysitis. Primary hypophysitis is mainly of lymphocytic, granulomatous, and xanthomatous types. Among the various primary hypophysitis, granulomatous hypophysitis is rare type with an incidence of 1 in 10 million. The various forms of hypophysitis are misdiagnosed as pituitary adenoma in 40% cases. Idiopathic granulomatous hypophysitis is even rarer inflammatory disorder accounting for <1% of cases involving panhypopituitarism with headache and visual disturbances. We report idiopathic granulomatous hypophysitis in a 28-year-old female presenting with blurring of vision and headache.